Roadblock Approach Method: Child Restraint System (CRS) Advocacy Program in Malaysia’s Rural Areas - N. Shaari; N. F. Paiman; M. A. Mohamad Radzi; N. Borhan; Y. Ahmad; F. Lamin; H. Makhpol (Journal of the Society of Automotive Engineers Malaysia, 2022)
The Child Restraint System (CRS) has been proven to reduce the injury severity and risk of fatality on children during road traffic crashes. This paper aimed to determine the awareness, usage, and compliance with the use of CRS. In addition, another objective was to determine the challenges of non-compliance use of CRS. In this advocacy program, the RTD (JPJ) enforcement team will set up roadblocks and the respondents were invited to participate in the advocacy program. The advocacy team was to provide advice and guidance on the correct use of CRS, promote and register CRS purchase subsidies and conduct a general study on awareness of the use of CRS among rural residents. As a result, more than 80% of respondents who join the advocacy program recognized CRS and almost 94% believed that CRS can reduce accidental injuries to children. 79.0% of them are interested in buying child safety seats if they are given a subsidy. More than 70% of the respondents agreed that the higher price of CRS, lack of awareness, and program are the factors that cause the lack of use of CRS. In conclusion, the use of CRS is lower in rural areas compared to urban areas. Even after CRS was made mandatory, the level of use is still at a moderate level.